Misguided and Deceptive Behavior of the Jinn Kafirs in Surah Al-Jin - Munaya Shofa; Yeti Dahliana (al-Afkar, Journal For Islamic Studies, 2024)
Surah Al-Jin is a makkiyah surah that totals 28 verses. This surah contains wisdom, and an explanation of who the Jinns are and also their details. This paper focuses on the testimony of Muslim jinns regarding the heretical behavior of infidel jinns in Surat al-Jin This research collected data using the library research method, referring to the sources of the Qur'an and tafsir as well as books related to the discussion. From the results of research, it is known that surah Al-Jin's discusses the attitude of the Jinns when hearing the reading of the Qur'an when it was first read by the Prophet Muhammad Saw. In this letter also mentions Jin's testimony of heresy that occurred in their realm. They also reported that there are two classes of jinns in the universe, those who believe in Allah Almighty and those who associate Allah Almighty. Furthermore, this letter contains the position of Prophet Muhammad (saw) as a messenger of Allah, as well as the position of the Jinn nation regarding supernatural matters. Neither the Prophet saw nor the Jinns knew anything unseen. Because only Allah Almighty is the key holder of unseen matters.